Bipolar hemiarthroplasty may reduce cerebrovascular accidents and improve early weight-bearing in the elderly after femoral neck fracture. Issue 4 (28th January 2022) - Dubin, Jeremy; Atzmon, Ran; Feldman, Viktor; Farkash, Uri; Nyska, Meir; Rath, Ehud; Palmanovich, Esequiel
Abstract : Abstract: Cerebrovascular accidents (CVA) in the elderly population after femoral neck fracture remain great concern for physicians. Specifically, surgical fixation techniques, such as bipolar hemiarthroplasty (HA) and internal fixation play a significant role in influencing the occurrence of postoperative CVA in the elderly population. In order to identify 2 cohorts, we used a rigid selection process based on our institution's database. The cohorts were comprised of a HA cohort and a cannulated screw cohort, of which underwent femoral neck surgery, performed by 3 fellowship trained surgeons from 2003 to 2014. Risk factors were documented and measured, including Coumadin use and hypertension, and postoperative complications such as CVA and death rate were also recorded. A P -value of <.05 was determined to be statistically significant. A power analysis was performed and achieved a power of 0.95. We found a non-significant reduction in CVA for bipolar HA (3.6% CVA vs 0.0% in the non-CVA group, P = .48) and a non-significant increase in CVA for cannulated screw use (7.6% CVA vs 14.4% in the non-CVA group, P = .11). In addition, we found a significant difference in terms of weight-bearing status at 6-weeks postoperatively (0.95 vs 2.0, P < .0001), favoring the bipolar HA group. Among the advantages of bipolar HA surgery, surgeons should consider its value in reducing the occurrence of postoperative CVA. Furthermore, patients who underwent bipolar HA had improved weight-bearing status postoperatively compared with cannulated screw fixation.